2019
DOI: 10.1259/bjr.20180774
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative diagnosis of osteoporosis using lumbar spine signal intensity in magnetic resonance imaging

Abstract: Osteoporosis is the reduction of bone mass and disruption of bone microarchitecture involving 55% of the population aged over 50 years. 1,2 Risk of osteoporotic fractures increases with reduction of bone mass density (BMD). 3 Osteoporosis is diagnosed using dual-energy X-ray absorptiometry (DXA) measuring bone mass density and is defined as T-score ≤−2.5 at hip, spine or femur. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…9 Despite the potential utility of the M-score, it is limited by the fact that it relies on signal-to-noise ratios that are specific to the MR system in use. 1,20 The original description by Bandirali et al noted that this limitation of the Mscore would require each center to identify its own set of normalized values, an arduous task that potentially limits the clinical utility of this score. 1 By contrast, the VBQ score described in the current study was implemented using MR volumes acquired by four distinct MR systems with no significant difference in VBQ scores between machines (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…9 Despite the potential utility of the M-score, it is limited by the fact that it relies on signal-to-noise ratios that are specific to the MR system in use. 1,20 The original description by Bandirali et al noted that this limitation of the Mscore would require each center to identify its own set of normalized values, an arduous task that potentially limits the clinical utility of this score. 1 By contrast, the VBQ score described in the current study was implemented using MR volumes acquired by four distinct MR systems with no significant difference in VBQ scores between machines (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The bone density is high, usually 300~3000HU [18]. Many studies have shown a good correlation between HU value and T score [8][9][10][18][19][20].Similarly, the M-score was the rst MRI-based observation to use adipose tissue with high T1 signal and to assess fat in ltration in cancellous bone by measuring T1 signal in the vertebral body [21].Other study has con rmed this approach and provided evidence for the use of m-scores to assess bone quality [22].However, M-Score is of limited utility because it requires measurements to be taken using the same MRI machine.Using the principle of M-score and avoiding its defects, VBQ score was developed [11]. VBQ score was standardized with L3 space CSF SI as a reference value and could be compared between patients with different MRI machines.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, opportunistic bone quality screening has been explored using lumbar MRIs, which are obtained at increasing rates due to the high prevalence of low back pain amongst the aging population [13,14,15]. The first such investigation, published by Bandirali et al in 2015, described the M-score, a SI measurement of the lumbar trabecular bone on T1-weighted MRI [13].…”
Section: Discussionmentioning
confidence: 99%
“…Using this logic, the authors evaluated a cohort of 226 women who underwent MRI and DXA scans and found that the M-score better correlated with fracture risk than did DXA scores [13]. Subsequent studies by other groups have validated this methodology, giving credence to the use of MRI for assessing bone quality [14,15]. Despite this, the M-score is limited in its utility as it requires all scores be acquired using the same MRI machine, as the score is standardized to the signal-to-noise ratio (SNR), which is specific to each individual MRI scanner.…”
Section: Discussionmentioning
confidence: 99%